Solve, giving your answer to 3 s.f. : 2^(2x) - 6(2^(x) ) + 5 = 0

22x - 6(2x ) + 5 = 0let y = 2xy2 - 6y + 5 = 0(y-5)(y-1) = 0 y=5, y=12x = 5, therefore, x = log25 = 2.32 (3 s.f.)2x = 1, therefore, x = log21 = 0

Answered by Jess O. Maths tutor

3948 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A curve has parametric equations x=t(t-1), y=4t/(1-t). The point S on the curve has parameter t=-1. Show that the tangent to the curve at S has equation x+3y+4=0.


Point P on the curve, x = 2tan( y+ π/12), has a y-coordinate of π/4. Find an equation for the normal to the curve at P.


Integrate the natural logarithm of x (ln x) with respect to x


Find the set of values for which: x^2 - 3x - 18 > 0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences